Diffusion tensor imaging in primary cervical dystonia. Issue 11 (14th October 2005) - Colosimo, C; Pantano, P; Calistri, V; Totaro, P; Fabbrini, G; Berardelli, A
Abstract : Background: It is the traditional view that primary dystonia arises from abnormal basal ganglia function but causes no apparent morphological changes. Objective: To determine whether cervical dystonia leads to ultrastructural changes in the brain, using diffusion tensor imaging to compare brain structure in 15 patients with cervical dystonia with 10 healthy controls. Design: Fractional anisotropy (FA) and mean diffusivity (MD) were obtained in 17 brain regions of interest. Results: Patients had higher FA values than controls in both putamina and lower FA values in the genu and in the body of the corpus callosum. Patients also had lower MD values in the left pallidum, the left putamen, and both caudati. Conclusions: In patients with cervical dystonia, diffusion tensor imaging shows ultrastructural changes in specific brain areas, including the basal ganglia.